MULTICULTURAL EDUCATION IN THE LEGISLATION SYSTEM - DiDik P. Wicaksono (Nurul Jadid University, 2016)
Multicultural education help students acquire knowledge, learn about attitudes, and skills needed to benefit Effectively in a pluralistic so- ciety and to berinteraksi, negotiate, and berkomunikasi with people from different groups with the aim of creating a civic and moral com- munity attitudes be better. Multicultural education in the implemen- tation, assuming the school and classroom run as a simulation of a real-life arena plural, constantly changing and evolving. Institutional schools and classrooms are alive with starring vehicle for learners and teachers at all educational staff acting as facilitators. Learning dia- logue and enrichment managed as a unique life experience, so that it can grow and experience the collective consciousness of every citizen and students who later Became the basis of political ethics based civic ethics.